Depressive Symptomatology, Psychological Stress, and Ovarian Reserve: A Role for Psychological Factors in Ovarian Aging? - Bleil, Maria E. (2012)
OBJECTIVE: To examine psychological factors in relation to antral follicle count (AFC), a marker of ovarian reserve, in a multiethnic sample of 683 pre-menopausal women in the Ovarian Aging (OVA) Study. METHODS: In cross-sectional analyses, linear regression was performed to determine whether AFC decline across women varied over levels of depression as well as depression in combination with psychological stress. The total and subscale scores of the Center for Epidemiological Studies Depression Scale (CESD) were used to measure depression and the Perceived Stress Scale was used to measure psychological stress. RESULTS: Following covariate-adjustment, the 2-way interaction of age-x-positive affect and the 3-way interaction of age-x-positive affect-x-stress were related to AFC (b = 0.047, p = .036; b = 0.012, p = .099, respectively). In stratified analyses, stress was related to AFC in women with low positive affect (b = −.070, p = .021) but not in women with high positive affect (b = .018, p = .54). AFC decline across women was progressively higher in women with low positive affect who reported low (−0.747 follicles/year), mid (−0.920 follicles/year), and high (−1.112 follicles/year) levels of stress. Results examining the CESD total and remaining subscale scores were all non-significant (p’s > .05). CONCLUSIONS: Cross-sectional evidence suggests that 1) women with low positive affect may experience accelerated AFC decline and 2) low positive affect may be a vulnerability factor, or, alternatively, high positive affect may be a protective factor, in moderating the negative effects of psychological stress on AFC decline.